2007
DOI: 10.1016/j.jaci.2006.10.015
|View full text |Cite
|
Sign up to set email alerts
|

Guideline-defining asthma clinical trials of the National Heart, Lung, and Blood Institute's Asthma Clinical Research Network and Childhood Asthma Research and Education Network

Abstract: Due to an increasing prevalence, morbidity and mortality associated with asthma, the National Heart, Lung and Blood Institute created the Asthma Clinical Research Network (ACRN) and the Childhood Asthma Research and Education (CARE) Network to improve public health. The objectives of these clinical research networks are to conduct multiple, well designed clinical trials for rapid evaluation of new and existing therapeutic approaches to asthma and to disseminate laboratory and clinical findings to the health ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 45 publications
(54 reference statements)
0
35
0
1
Order By: Relevance
“…The exacerbation of asthma was defined by the persistence of the crisis beyond 24 hours. As before, this exacerbation was classified as a mild, moderate and severe crisis [6] [7].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The exacerbation of asthma was defined by the persistence of the crisis beyond 24 hours. As before, this exacerbation was classified as a mild, moderate and severe crisis [6] [7].…”
Section: Methodsmentioning
confidence: 99%
“…It is now admitted [6] [22] [23], on the one hand that short-acting β-mimetics are first-line treatment irrespective of the age of the child or the level of severity of the crisis, and on the other that their preferred way of administration is the inhaled route.…”
Section: Therapeutic Aspects and Evolutionmentioning
confidence: 99%
“…Details of these trials have been previously published (28)(29)(30). Table E1 in the online supplement also has basic descriptors of these cohorts.…”
Section: Human Subject Participationmentioning
confidence: 99%
“…The networks have been successful doing this and also recognizing variability of treatment response, factors that modify response to treatment, and potential predictors of treatment response, such as biomarkers and genetics. The accomplishments of ACRN and the CARE Network over the past 15 years were summarized in a review by Denlinger et al 17 One of the recent ACRN trials attempted to identify asthma characteristics and biomarkers associated with ICS response in adults. 18 This study found that the only strong predictors of ICS response were albuterol reversibility and FEV 1 /forced vital capacity.…”
Section: Responsivenessmentioning
confidence: 99%